Development of prognostic signature and nomogram for patients with breast cancer. Issue 11 (March 2019) - Su, Jiao; Miao, Li-Feng; Ye, Xiang-Hua; Cui, Meng-Shen; He, Xiao-Feng
Abstract : Abstract: To identify prognostic signature that could predict the survival of patients with breast cancer (BC). Breast cancer samples and normal breast tissues in the TCGA-BRCA and GSE7390 were included. Differentially expressed genes (DEGs) were identified using the "limma" method. Overall survival (OS) associated with DEGs were obtained using univariate and multivariable Cox proportional-hazards regression analysis, and the corresponding prognostic signature and nomogram were constructed. Calibration analysis and decision curve analysis (DCA) were performed. In all, 742 DEGs were identified, 19 of which were independently correlated with the OS of BC patients. The OS of patients in the 19-gene signature low-risk group was significantly better than that in high-risk group (hazard ratio [HR] 0.3506, 95% confidence interval [CI] 0.2488–0.4939), and the 19-gene based signature was demonstrated to be an independent prognostic factor in patient with BC in the TCGA-BRCA cohort (HR 1.501, 95% CI 1.374–1.640) and validation cohort GSE7392 ((HR 0.3557, 95% CI 0.2155–0.5871, P < .0001)). The primary and internally validated C-indexes for the 19-gene signature-based nomogram were 0.817 and 8.013, respectively. The results of calibration analysis and DCA analysis confirmed the robustness and the clinical usability of the nomogram. We constructed a prognostic signature and nomogram for patient with BC, which showed good application prospect. Abstract : Supplemental Digital Content is available in the text